AN ANALYSIS OF HOTEL RATING AND ITS IMPLICATION ON FINANCIAL TURNOVER OF RATED HOTELS IN KENYA - KIPLAGAT, WILSON KIBET; MAKINDI, STANLEY; OBWOYERE, GILBERT OBATI (International Journal of Environment, Ecology, 2014)
Hotel service quality has long been a concern for scholars and practitioners. Previous researches indicate that the service quality of hotels in Kenya is yet to match international standards. It has been argued that one reason why hotels do not deliver quality service is due to the substantial gap of the living standards of Kenyans and international tourists and the lack of proper investment in the sector due to fluctuations in growth in the past. The purpose of the study was to examine the financial implications of rating of hotels. The study was conducted in tourism establishments in Nairobi and parts of Rift Valley and it focused on rated hotels in Kenya. The research design used sociological survey targeting 50 hotel establishments. The researcher relied on primary and secondary data for information from which an analysis was conducted and conclusions deduced. The primary data was collected through face-to-face interviews among tourists and hotel managers using a structured questionnaire. The quantitative data from the questionnaires was analyzed using Statistical Package for the Social Sciences and Ms Excel. Findings from the study pointed out a strong relationship between hotel rating and hotel revenues. This was evidence that for hotels to increase earnings they also needed to improve their ratings. Further to this, rating of establishments eased the decision making of tourists since they would easily differentiate service level of hotels. Overall, it was evident that hotel rating was vital in the hotel business as it aided establishments effectively compete in the market place. Findings from the study will therefore offer an unobtrusive and economic way of examining hotel service quality. In addition, it will also help in understanding the quality service of the star rated hotels perceived by the domestic tourists and financial implication to hotel establishments.
Keywords: Hotel Rating; Financial Turnover